2012
DOI: 10.1021/la301738p
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Water Confined in Porous Calcium-Silicate-Hydrates

Abstract: Water within pores of cementitious materials plays a crucial role in the damage processes of cement pastes, particularly in the binding material comprising calcium-silicate-hydrates (C-S-H). Here, we employed Grand Canonical Monte Carlo simulations to investigate the properties of water confined at ambient temperature within and between C-S-H nanoparticles or "grains" as a function of the relative humidity (%RH). We address the effect of water on the cohesion of cement pastes by computing fluid internal pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
151
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(160 citation statements)
references
References 63 publications
8
151
0
1
Order By: Relevance
“…The 15% RH threshold differs slightly from the reference point of 11% described above, which is based on an estimate of the RH at which the adsorbed layer on the pore surface is one molecule thick [37,38], not specifically on a threshold between gel pore and interlayer water removal. The existence of a threshold RH for interlayer water desorption is supported by some of the present authors' molecular-scale simulations [21,22], as shown in Figs. 3(a)-3(c) and by NMR experiments [31], as shown in Fig. 3(c).…”
Section: Interlayer Watersupporting
confidence: 82%
See 2 more Smart Citations
“…The 15% RH threshold differs slightly from the reference point of 11% described above, which is based on an estimate of the RH at which the adsorbed layer on the pore surface is one molecule thick [37,38], not specifically on a threshold between gel pore and interlayer water removal. The existence of a threshold RH for interlayer water desorption is supported by some of the present authors' molecular-scale simulations [21,22], as shown in Figs. 3(a)-3(c) and by NMR experiments [31], as shown in Fig. 3(c).…”
Section: Interlayer Watersupporting
confidence: 82%
“…At present, connections between measured sorption isotherms, pore structure, and associated properties rely on models that link the evaporation and condensation of water at a given RH with the width and connectedness of the pores over a range of scales [18,19,21,22]. Models for mesoporous materials are typically extensions of the Kelvin-Laplace theory, which links the RH with the width of pores being emptied or filled and with the pore pressure causing volumetric strain [23,24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This potential has a Coulombic part, Van der Waals interactions, as well as harmonic bonds for hydroxyl groups and harmonic angular springs for water. The C-S-H and nanopore models built with this potential have been thoroughly validated against experiments [25,26]. All the parameters for the CSHFF are as described in Ref.…”
Section: A Interaction Force Fieldmentioning
confidence: 99%
“…The model described in Ref. [25] is used. This is a 2.483 nm C-S-H configuration containing a gel pore at 100% humidity.…”
Section: Sorption Of Csmentioning
confidence: 99%